Acceptance and commitment therapy : the clinician's guide for supporting parents / Koa Whittingham, Lisa W. Coyne. - Whittingham, Koa; Coyne, Lisa W. (Academic Press, 2019)
'Acceptance and Commitment Therapy' constitutes a principles-based guide for clinicians to support parents across various stages of child and adolescent development. It uses Acceptance and Commitment Therapy (ACT) as an axis to integrate evolution science, behaviour analysis, attachment theory, emotion-focused and compassion-focused therapies into a cohesive framework. From this integrated framework, the authors explore practice through presenting specific techniques, experiential exercises, and clinical case studies.